Sizing and Mission Profile Analysis of the Hybrid-Electric Propulsion System for Retrofitting a Fixed Wing VTOL Aircraft - Jianan Zong; Bingjie Zhu; Zhongxi Hou; Xixiang Yang; Jiaqi Zhai (International Journal of Aerospace Engineering)
Hybrid-electric technology can be expected to improve the performance of fixed wing vertical takeoff and landing (VTOL) aircraft. In this paper, we demonstrated a method of retrofitting a single-energy propulsion system prototype with a hybrid-electric propulsion system. Since the hybrid-electric system has several working modes, the optimal design results have strong coupling with mission performance. Therefore, we propose an analysis method of the mission profile to determine the design point. Finally, the payload-range sensitivity is studied. The results show that the hybrid-electric propulsion system can greatly increase the mission profile of aircraft. The analysis method of the mission profile also provides perspective for the hybrid-electric propulsion system design.